Acute toxic encephalopathy following bromadiolone intoxication: a case report - Quan Li; Wei Yu; Yun Qu; Jin-Qiu Wang; Ning Mao; Hai Kang (BMC Neurology, 2021)
Abstract Background Clinically, bromadiolone poisoning is characterized by severe bleeding complications in various organs and tissues. Bromadiolone-induced toxic encephalopathy is extremely rare. Here, we report a special case of bromadiolone-induced reversible toxic encephalopathy in a patient who had symmetrical lesions in the deep white matter. Case presentation A 23-year-old woman mainly presented with dizziness, fatigue, alalia and unsteady gait after the ingestion of bromadiolone. The laboratory examinations showed normal coagulation levels. Brain magnetic resonance imaging (MRI) showed apparent diffusion restriction in the bilateral deep white matter. The clinical manifestations and MRI alterations were reversible within one month of treatment with vitamin K. The neuropsychological assessment showed no neurodegenerative changes at the 2-year follow-up. Conclusion With the increased use of bromadiolone as a rodenticide, more cases of ingestion have been reported annually over the past several years. Bromadiolone-induced toxic encephalopathy has no special clinical manifestations and is potentially reversible with timely treatment. Because of the reversible restricted diffusion on diffusion-weighted images (DWI) and low apparent diffusion coefficient (ADC) values, transient intramyelinic cytotoxic oedema is thought to be the cause rather than persistent ischaemia. The underlying pathophysiological mechanism is still unknown and may be coagulant-independent. This clinical case extends the current knowledge about neurotoxicity in cases of bromadiolone poisoning and indicates that MRI is useful for the early detection of bromadiolone-induced toxic encephalopathy.